Pengaruh Profitabilitas dan Likuiditas terhadap Struktur Modal pada Perusahaan Manufaktur Sektor Industri Dasar dan Bahan Kimia - Octaviani, Febi; Warsitasari, Wahyu Dwi (Politeknik Negeri Padang, 2022)
This research aims to see the influence of profitability and liquidity on the capital structure of manufacturing companies listed on the IDX in the basic and chemical industries for the period 2018-2020. This research takes quantitative techniques and is a type of associative research. The population is 10 manufacturing companies that have been registered with the IDX of the basic industrial and chemical sectors for the period 2018 - 2020 which can be accessed in the www.idx.co.id. The data analysis techniques used in this study are descriptive statistics and panel data regeresi analysis using the Eviews 9 program. Based on the results of research conducted by analyzing the regression of panel data in the above research that explains the profitability and liquidity of the capital structure, it can be concluded that the results of the test show that profitability has no effect on the capital structure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) industrial sector.